Letter (copy) : Caps for the Basque children - Tewson, Vincent
037-0172-001 HVT/FC/576. Secretary's. 26th May, 1937. Mr. Sams, The Basque Children's Camp, North Stoneham, SOUTHAMPTON. Dear Mr. Sams, CAPS FOR THE BASQUE CHILDREN. A Mr. Hall, who is a schoolmaster of Ilford, has offered to send 300-400 caps for the Basque Children. Mr. Hall has been running camps for boys where they have worn special caps. He has no further use for the caps and has asked whether they would be acceptable at the Basque Camp. I have been in touch with Marsham Street and have been asked to have the caps sent on to you. I have passed the word on to Mr. Hall, and he will be despatching them to you. My very best wishes in your great work. Yours sincerely, Assistant Secretary. 292/946/37/172